Correlation between levels of vitamins D3 and E in type 2 diabetes mellitus: a case-control study in Serdang, Selangor, Malaysia - Md Razip, Nurliyana Najwa; Gopalsamy, Banulata; Abdul Mutalib, Mohd Sokhini; Sui, Kiat Chang; Abdullah, Muhammad Mikhail Joseph Anthony; Azlan, Azrina; Rejali, Zulida; Khaza’ai, Huzwah (Multidisciplinary Digital Publishing Institute, 2021)
An overview of vitamins D3 and E suggests micronutrient deficiency contributes to type 2 diabetes mellitus (T2DM). A case-control study was conducted to determine the status of plasma vitamins D3 and E isomers amongst diabetic Malaysians. Two groups were recruited for participation, one comprising fifty diabetic subjects (DM) and one comprising fifty non-diabetic (non-DM) subjects, in order to assess their plasma vitamin D3, calcium and vitamin E status. Glycaemic status (haemoglobin A1c, HbA1c; fasting blood glucose, FBG; C-Peptide) and lipid profiles (total cholesterol, TC; triglycerides, TG; low-density lipoprotein-cholesterol, LDL-C; high-density lipoprotein-cholesterol, HDL-C) were assessed, followed by anthropometric measurements. The Mann–Whitney U-test, Kruskal–Wallis and Spearman’s correlation coefficient were used to elucidate the association between levels of plasma vitamins D3 and E and T2DM. The vitamin D3 deficiency group (<20 ng/mL) showed a significant correlation (p < 0.05) with glycaemic status (HbA1c and FBG) and lipid profiles (HDL-C, LDL and TC). Spearman’s correlation demonstrated that vitamin D3 status is strongly correlated with HDL levels (p < 0.05). Similarly, plasma total vitamin E levels >4.9 μg/mL revealed significantly different FBG, HbA1c, C-Peptide, LDL, HDL and TC levels across both groups. Moreover, family history, smoking, waist circumference and HbA1c levels demonstrated a significant association (p < 0.05) with levels of vitamins D and E but not FBG and lipid profiles. This could be because the pre-diabetic status among the non-DM group influenced the outcomes of this study.